Struggle For Equality As Seen In Carol Ann Duffy’s Poem “Little Red Cap” - Paputungan, Vennalizha S.; Rorintulus, Olga; Andries, Fivy (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2025)
The objective of this research is to elucidate the portrayal of the battle for equality in the poem "Little Red Cap." The present study employed a qualitative research design as it focused on collecting data in the form of fully descriptive words. The data utilised in this analysis draws upon feminist literary theory. The primary source for this analysis is the poem "Little Red Cap" by Carol Ann Duffy. Additionally, various secondary sources, including books, journals, and other references, have been consulted to provide further support for this research. The findings of the study revealed the manifestation of women's pursuit for equal rights, as shown in Carol Ann Duffy's poem "Little Red Cap." The protagonist, "Little Red Cap," demonstrates her ability to resist and challenge patriarchal norms, ultimately achieving a significant triumph in affirming women's capacity to transcend patriarchal constraints and assert their ambitions and autonomy.